Improving the Flame Retardancy of Bamboo Slices by Coating With Melamine–Phytate via Layer-by-Layer Assembly - Lin, Peng; Xu, Yuchen; Hou, Junfeng; Zhang, Xiaochun; Ma, Lingfei; Che, Wenbo; Yu, Youming (Frontiers in Materials, 2021)
Bamboo is a rich natural resource in the Asia Pacific, its widely used in the construction and decoration industry. Meanwhile, bamboo is an extremely combustible natural polymer material. Herein, the bamboo slices were treated with melamine (MEL) and phytic acid (PA) by layer-by-layer (LBL) assembly technology to improve its flame retardancy properties. The morphology and chemical composition of untreated and treated bamboo slices were measured by scanning electron microscopy (SEM) equipped with Energy Dispersive X-ray (EDX) analysis and Fourier transform infrared (FTIR) spectra. The results showed that two-dimensional melamine-phytate (MPA) nanoflakes were successfully formed and deposited on the bamboo surface. The deposition of MPA coating caused earlier degradation of bamboo to form char, according to thermo-gravimetric analysis (TGA). The peak heat release rates (HRR) of the treated bamboo slices were reduced by more than 28% compared to the untreated ones. The MPA's catalytic effect on the formation of thermally stable char was responsible for the significant improvement in flame retardant. Besides, the char layer with excellent thermal resistance performed a vital role in suppressing flame spread.